A faculdade do juízo no pensamento político de Hannali Arendt - Jose Luiz de Oliveira (2001)
The objective of our dissertation is the exphcitation of the paper of the abihty of the judgement kantian in Hannah Arendt political thought. The starting point of its political thought is expressed in the totalitarian phenomenon, that had as consequences; the destruction of the public space, the suppression of the freedom, the condemnation to the isolation and the destruction of the human capacities of thinking and of judging. The ability of the judgement kantian, reinterpreted for Hannah Arendt, is through its concepts a crucial theme for the basement of a political philosophy capable to oppose to the totalitarianism. When appropriating of the legacy of Third Critical Kantian, Hannah Arendt founds starting from there, its political philosophy.